A qualitative study of older refugees' perception and attitudes towards dementia and dementia risk reduction during the COVID‐19 pandemic. (20th December 2022) - Al‐Rousan, Tala; Awad, Mina; Sideman, Alissa Bernstein; Moore, Alison A.
Abstract: Background: The COVID‐19 pandemic continues to worsen economic inequality, political unrest and violence resulting in unprecedented numbers of refugees and asylees globally. Various stressors related to forced displacement may impact cognitive function as refugees age in hosting countries. However, little is known about how forced displacement impacts perceptions and attitudes towards dementia and dementia risk reduction. Method: In‐depth interviews with 61 older refugees aged 55‐86 who were resettled in San Diego, California from Iraq and Syria, conducted between April‐December of 2021. A phenomenological long‐table approach was used to identify themes and categorize data on dementia knowledge, risk and attitudes. Result: The mean age of participants was 64.61 (SD: 7.19), 50.82% were female, 14.75% were employed, Median income was USD $15, 001 ‐ %25, 000, median years since resettlement was 8 (SD7.06), 32.79% reported they could read and write English, 81.97% were Iraqis, 80.33% were married was. 16.39% have contracted COVID‐19, and 85.25% reported being more forgetful since the pandemic started. Participants' responses about their attitudes about dementia were classified into three distinctive thematic domains: fear, acceptance, and practical challenges. Participants identified fear of developing dementia and the need to improve dementia knowledge as major motivators towards adopting healthier lifestyle and health behaviors. Acceptance emerged in relationship to the following areas: 1) religious; aging mentioned in the holy books as an experience associated with feelings of humiliation and helplessness, 2) cultural; dementia as an unavoidable part of normal aging, 3) experiential; displacement and war‐related trauma increase risk of dementia. Practical challenges included the lack of age‐friendly and trauma‐informed care and services available for refugees which were identified as a major barrier for preventive, behavioral and lifestyle change. Conclusion: These findings can be used to develop effective and refugee‐focused interventions that increase motivators and reduce barriers by tailoring interventions to refugees' dementia risk reduction literacy and motivations to change behaviors.